Post-treatment of rat aflatoxicosis by camel milk and silymarin - Hassaneen, Nahla H.; Hemeda, Shabaan A.; El Nahas, Abeer F.; Albadrani, Ghadeer M.; Al-Ghadi, Muath Q.; Mohammedsaleh, Zuhair M.; Fadl, Sabreen E.; El-Diasty, Eman M.; Sakr, Hader I. (Frontiers in Pharmacology, 2025)
BackgroundAflatoxins are highly potent mycotoxins that can seriously harm the health of humans and a variety of animal species. On the other hand, camel milk and silymarin offer a variety of positive effects for many animal species. In addition, camel milk and silymarin reduce the impact of AFB1 on the hematology, serum biochemical markers, histopathology of the liver and testes, and expression of the inflammatory, antioxidant, and male reproductive genes.Methods40 rats were used to evaluate the beneficial effect of silymarin and camel milk against aflatoxin B1 (AFB1) toxicity in rats. The classified treatments were the control negative (no treatment) and the control positive (supplied with 1.4 mg aflatoxin/kg diet) for 28 days. Camel milk group (supplied with 1.4 mg aflatoxin/kg diet) for 28 days and camel milk (1 milliliter of camel milk per kilogram of body weight) orally, from day 29 to day 43). Silymarin (supplied with 1.4 mg aflatoxin/kg diet) for 28 days and silymarin (20 mg silymarin/kg b.wt), orally, from day 29 to day 43). The evaluation was done through measuring leukocyte count, liver function tests, carcinoembryonic antigen (CEA), alpha-fetoprotein (AFP), ferritin, and testosterone. Moreover, the histopathology of the liver and testes was done along with expression levels of specific genes in the liver and testes.ResultsThe outcomes showed that the post-treatment with silymarin and camel milk improved biochemical markers in serum and ability to reproduce.ConclusionIn conclusion, post-treatment with camel milk and silymarin could mitigate the negative effect of AFB1 on rats.